2022
DOI: 10.3390/toxins14100711
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium botulinum C3 Toxin for Selective Delivery of Cargo into Dendritic Cells and Macrophages

Abstract: The protein toxin C3bot from Clostridium botulinum is a mono-ADP-ribosyltransferase that selectively intoxicates monocyte-derived cells such as macrophages, osteoclasts, and dendritic cells (DCs) by cytosolic modification of Rho-A, -B, and -C. Here, we investigated the application of C3bot as well as its non-toxic variant C3botE174Q as transporters for selective delivery of cargo molecules into macrophages and DCs. C3bot and C3botE174Q facilitated the uptake of eGFP into early endosomes of human-monocyte-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Note that these times refer to the (chase) time elapsed after an initial 15 min (pulse) period when the toxin was allowed to bind to the plasma membrane before washing. These findings are therefore roughly consistent with those recently reported by Fellermann et al, who found that 70-100% of C3 toxin from Clostridium botulinum is associated with early endosomes of human macrophages after 30 min (Fellermann et al, 2022). Accordingly, at this stage C3bot displays a punctate pattern that resembles that of C3larvinA at a comparable total time.…”
Section: Discussionsupporting
confidence: 93%
“…Note that these times refer to the (chase) time elapsed after an initial 15 min (pulse) period when the toxin was allowed to bind to the plasma membrane before washing. These findings are therefore roughly consistent with those recently reported by Fellermann et al, who found that 70-100% of C3 toxin from Clostridium botulinum is associated with early endosomes of human macrophages after 30 min (Fellermann et al, 2022). Accordingly, at this stage C3bot displays a punctate pattern that resembles that of C3larvinA at a comparable total time.…”
Section: Discussionsupporting
confidence: 93%
“…STED-microscopy was performed as described in [ 61 , 62 ]. A total of 1.8 × 10 5 HeLa cells were seeded per well in an 8-well µ-slide with glass bottom (ibidi GmbH, Gräfelfing, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…For better visualization, a σ = 1 pixel Gaussian blur and >20 count intensity threshold were applied. A self-written search algorithm (Python 3.7, available on request) was used to count the eGFP signals, as described earlier [ 61 ], and a threshold of 10 counts was applied. For each experiment, the mean number of eGFP signals was calculated and averaged for five individual experiments ( n = 5).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the shortening of lysozyme to Lys-H1 may affect and limit its antimycobacterial activity. The uptake and trafficking of lysozyme or its derivatives could be improved by engineering delivery vehicles that specifically target macrophages [12] and support the migration of effector molecules into the mycobacterial compartment. The efficacy of this approach has been recently demonstrated for the endogenous antimycobacterial peptides gran1…”
Section: Lysozyme Is a Prominent Antimycobacterial Protein In Human H...mentioning
confidence: 99%